Onion-inspired MXene/chitosan-quercetin multilayers: Enhanced response to H2O molecules for wearable human physiological monitoring - Li, Xin; Lu, Yanli; Shi, Zhenghan; Liu, Guang; Xu, Gang; An, Zijian; Xing, Huan; Chen, Qingmei; Han, Ray P.S.; Liu, Qingjun (Sensors and actuators. B, Chemical, 2021)
•Ultrathin MXene/chitosan-quercetin multilayers were assembled for humidity detection.•Superior sensitivity and ultrafast response for water molecules was realized.•A fully wearable tag was made to implement human physiological monitoring.•The multilayers can track human respiration in real time and high resolution. Two-dimensional (2D) materials provides large surface area for H2O molecules adsorption and interaction, which has been utilized in humidity sensing and noninvasive monitoring of physiological events such as respiration. However, disadvantages including slow response or modest response hinder the accurate tracking of human breath. Hence, MXene, the new member of 2D material family with excellent hydrophilicity and tunable conductivity, has drawn much attention. In this work, the enhanced response of Ti3C2Tx MXene to H2O molecules was achieved by onion-inspired assembling of Ti3C2Tx MXene and chitosan-quercetin hybrid layer-by-layer. The chitosan-quercetin modified multilayers suppress the degradation of MXene in environment, exhibiting superior response (317 % at 90 % RH), ultrafast response (0.75 s), and long-term stability (more than 15 days). Integrated with a wireless flexible detecting tag, the multilayers realized wearable human respiration monitoring with robust, accurate tracking capacity, offering a facile and feasible method for versatile physiological monitoring based on humidity sensing.